Analysis Analysis of Ethno-STEM-Integrated PBL E-Module to Enhance Creative Thinking Skills of 8th Grade Junior High School Students - Almira, Hening Tyas; Yamtinah, Sri; Masykuri, Mohammad (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research aims to analyze the needs for developing an Ethno-STEM-integrated Problem-Based Learning (PBL) e-module to enhance the creative thinking skills of 8th-grade junior high school students on the topics of vibrations, waves, and sound. Methodology: This study employed a mixed method. The instrument used was a questionnaire adapted from previous research. The sample consisted of junior high school science teachers and students in Karanganyar Regency. Data analysis used descriptive statistics. Main Findings: The findings revealed a significant gap between current science learning practices and the demands of 21st-century education. Teachers reported difficulties in explaining abstract concepts such as vibrations, waves, and sound using conventional methods, compounded by the limited availability of instructional media that integrates local cultural wisdom. Meanwhile, students expressed strong interest in digital and contextual learning resources, yet their creative thinking skills remained low, with an average score of only 49.4%. This indicates the urgent need for innovative, interactive, and culturally relevant learning solutions. Novelty/Originality of this Study: The development of an Ethno-STEM-based PBL e-module that not only integrates science, technology, engineering, and mathematics with local wisdom but also explicitly targets the four core aspects of creative thinking: fluency, flexibility, originality, and elaboration. Unlike conventional modules, this approach leverages ethnoscience contexts to make abstract concepts more tangible while simultaneously fostering problem-solving and higher-order thinking. Thus, the research provides a strategic foundation for designing learning media that is pedagogically sound, culturally meaningful, and aligned with the competencies required in the global era.